Jackson Pollock - Blind Spots [on the occasion of the exhibition ... Tate Liverpool, 30 June - 18 October 2015 ; Dallas Museum of Art, 20 November 2015 - 20 March 2016] - Delahunty, Gavin 1977- (Tate Publishing, 2015)
Jackson Pollock was one of the most influential and provocative American artists of the twentieth century. This fully illustrated publication accompanies the first exhibition in over three decades of a crucial phase of his work, referred to as the Black Pourings. This controversial body of black enamel and oil paintings, which were exceptional in their absolute merging of colour and surface, are accompanied here by drawings that are regarded as his most important and productive as a draughtsman